2021
DOI: 10.1101/2021.05.27.445991
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Metformin Suppresses Monocyte Immunometabolic Activation by SARS-CoV-2 and Spike Protein Subunit 1

Abstract: A hallmark of COVID-19 is a hyperinflammatory state that is associated with severity. Various anti-inflammatory therapeutics have shown mixed efficacy in treating COVID-19, and the mechanisms by which hyperinflammation occurs are not well understood. Previous research indicated that monocytes, a key innate immune cell, undergo metabolic reprogramming and produce inflammatory cytokines when stimulated with SARS-CoV-2. We hypothesized that binding by the viral spike protein mediates this effect, and that drugs w… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 96 publications
0
6
1
Order By: Relevance
“…Metformin injection in SARS‐CoV‐2 infected hACE2 transgenic mice improved the morbidity and rescued the mice from ARDS 258 . In an in vitro setting, it was also demonstrated that metformin results in the rescue of monocytes from inflammation 255 …”
Section: Immunomodulatory Drugs For Acute Covid‐19mentioning
confidence: 92%
See 3 more Smart Citations
“…Metformin injection in SARS‐CoV‐2 infected hACE2 transgenic mice improved the morbidity and rescued the mice from ARDS 258 . In an in vitro setting, it was also demonstrated that metformin results in the rescue of monocytes from inflammation 255 …”
Section: Immunomodulatory Drugs For Acute Covid‐19mentioning
confidence: 92%
“…258 In an in vitro setting, it was also demonstrated that metformin results in the rescue of monocytes from inflammation. 255 However, in clinical trials, metformin showed uncertainty. In a retrospective cohort analysis, the use of metformin was not associated with a reduced risk of mortality in total samples of both men and women from COVID-19.…”
Section: Metforminmentioning
confidence: 99%
See 2 more Smart Citations
“…All raw data and analytical scripts (as R markdown files) are available in a dedicated FigShare repository ( 49 ). This manuscript was posted to the preprint server bioRxiv prior to submission for publication ( 52 ).…”
Section: Methodsmentioning
confidence: 99%